2008
DOI: 10.1007/s11695-007-9292-y
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Maltreatment and Psychiatric Morbidity in Bariatric Surgery Candidates

Abstract: This study confirms high rates of childhood maltreatment in patients presenting for bariatric surgery that are associated with increased prevalence of lifetime mood, anxiety, and substance use disorders. Future prospective studies should include evaluation of a broad range of mental health and childhood experiences to tease apart the nature of the relationships between these factors and their potential impact on post-surgical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(43 citation statements)
references
References 37 publications
3
34
1
5
Order By: Relevance
“…The attained rates were compared to previously reported studies that used BSPs as well as to studies using obese, non-BSPs and studies using the general population. Additionally, similar to previous findings, it is hypothesized that BSPs who disclose a history of sexual abuse/attack will be more likely to disclose histories of physical abuse, psychological problems, psychological treatment, psychiatric treatment, psychiatric hospitalization, and suicidal ideation (Clark et al, 2007;Grilo et al, 2005;Gustafson et al, 2006;Wildes et …”
Section: Current Studymentioning
confidence: 61%
See 1 more Smart Citation
“…The attained rates were compared to previously reported studies that used BSPs as well as to studies using obese, non-BSPs and studies using the general population. Additionally, similar to previous findings, it is hypothesized that BSPs who disclose a history of sexual abuse/attack will be more likely to disclose histories of physical abuse, psychological problems, psychological treatment, psychiatric treatment, psychiatric hospitalization, and suicidal ideation (Clark et al, 2007;Grilo et al, 2005;Gustafson et al, 2006;Wildes et …”
Section: Current Studymentioning
confidence: 61%
“…Were the patients given any explanation of why sexual abuse/attack was being assessed and how this information might affect surgical clearance? The two studies that did report this information (Oppong et al, 2006;Wildes, Kalarchian, Marcus, Levine, & Courcoulas, 2008) informed the patients that the assessment of sexual abuse/attack was independent of surgical clearance. Interestingly, these two studies also reported prevalence rates of sexual abuse/attack that were higher than most other studies using BSPs (26.7% and 31% respectively).…”
Section: Assessing Sexual Abuse/attack: Patient Variablesmentioning
confidence: 99%
“…Childhood sexual abuse and maltreatment, while more prevalent in the severely obese population (Grilo et al, 2005;Wildes, Kalarchian, Marcus, Levine, & Courcoulas, 2008), do not appear to have any relationship with postsurgical weight loss (Fujioka, Yan, Wang, & Li, 2008;Grilo, White, Masheb, Rothschild, & Burke-Martindale, 2006). Presurgical life stress, in and of itself, does not appear to have a negative impact on weight loss (Herpertz et al, 2004;van Hout et al, 2005).…”
Section: What Is Known -Paradoxical Resultsmentioning
confidence: 97%
“…Bariatric patients with a history of childhood trauma may also have a higher rate of mood or substance disorders, which can recur or become exacerbated after surgery. 39 Although victims of childhood trauma may lose equivalent amounts of weight within the first year after surgery, quality of life and psychosocial complications (including rates of psychiatric hospitalization) may be more problematic for them. 40 It is important for these patients to be educated about the possibility that they may feel more vulnerable after losing a significant amount of weight and to have a treatment plan in place should that occur.…”
Section: 34mentioning
confidence: 99%